Ca2+ waves in astrocytes: computational modeling and experimental data - Musotto, Rosa; Wanderlingh, Ulderico; Pioggia, Giovanni (Frontiers in Cellular Neuroscience, 2025)
This paper examines different computational models for Calcium wave propagation in astrocytes. Through a comparative analysis of models by Goldbeter, De Young-Keizer, Atri, Li-Rinzel, and De Pittà and of experimental data, the study highlights the model contributions for the understanding of Calcium dynamics. Tracing the evolution from simple to complex models, this work emphasizes the importance of integrating experimental data in order to further refine these models. The results allow to improve our understanding of the physiological functions of astrocytes, suggesting the importance of more accurate astrocyte models.